Mapping the contemporary fertilizer policy landscape in Malawi: a guide for policy researchers - Aberman, Noora-Lisa; Johnson, Michael E.; Droppelmann, Klaus; Schiffer, Eva; Birner, Regina; Gaff, Peter (International Food Policy Research Institute, 2012)
A major rationale for conducting policy research is the contribution the results can make to policy improvement efforts. Over the years, funders of international policy research have placed increasing emphasis on making sure that the research they fund influences policymaking, challenging research organizations to document the impact of their research. To improve the integration of research into policy, stakeholders need to understand the policy process itself.